Alemtuzumab for multiple sclerosis: Long term follow-up in a multi-centre cohort. (August 2016) - Willis, MD; Harding, KE; Pickersgill, TP; Wardle, M; Pearson, OR; Scolding, NJ; Smee, J; Robertson, NP
Background: Alemtuzumab has recently been approved for treatment of relapsing MS, but concerns remain about its use since long-term studies of adverse events remain limited. Furthermore, a clear understanding of its application and durability of effect in clinical practice has yet to evolve. Objectives: To investigate long-term efficacy and safety outcomes in a multicentre cohort of patients treated with alemtuzumab. Methods: Patients treated from 2000 and followed-up at three regional centres were identified. Baseline and prospective data were obtained and validated by clinical record review. Results: One hundred patients were identified with a mean follow-up of 6.1 years (range 1–13). Forty patients were retreated with at least one further treatment cycle. Annualized relapse rates fell from 2.1 to 0.2 ( p <0.0001) post-treatment and were sustained for up to eight years of follow-up. Mean change in EDSS score was +0.14. Forty-seven patients developed secondary autoimmunity. Conclusion: Observed reduction in relapse rates reflected those reported in clinical trials, but we were unable to corroborate previous observations of disability reversal. 40% of patients required additional treatment cycles. Autoimmune adverse events were common, occurring at a higher rate than previously reported, but were largely predictable, and could be managed effectively within a rigorous monitoring regime.